RESULTS AFTER IMMUNOTARGETED TREATMENT IN LARYNGEAL PAPILLOMATOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Recurrent laryngeal papillomatosis (RLP) is a chronic proliferative disease of the respiratory epithelium caused predominantly by human papillomavirus types 6 and 11. The disease is characterized by repeated growth of benign papillomatous lesions in the larynx, leading to dysphonia, airway obstruction, and frequent surgical interventions. Conventional management relies primarily on microlaryngoscopic excision; however, recurrence rates remain high, particularly in juvenile-onset cases. Immunotargeted therapy has emerged as a promising adjunctive strategy aimed at modulating host immune responses and suppressing viral persistence. This article presents a comprehensive theoretical and analytical review of the results observed after immunotargeted treatment in RLP. Based on data from published clinical studies, dissertations, and immunological research, the paper evaluates recurrence frequency, inter-surgical intervals, viral load reduction, cytokine modulation, and overall quality-of-life improvements. Statistical trends indicate that adjuvant immunotherapies, including interferon-based regimens, therapeutic HPV vaccination, and monoclonal antibody approaches targeting angiogenic pathways, may reduce recurrence rates by 30–60% in selected patient populations. Moreover, immunomodulatory strategies appear to prolong remission intervals and decrease the number of annual surgical procedures. The analysis integrates immunopathogenetic mechanisms underlying RLP with clinical outcome data, emphasizing the role of T-cell dysfunction, local cytokine imbalance, and viral immune evasion. The findings support a multidisciplinary therapeutic model combining surgery with immunotargeted interventions. The article concludes that immunotherapy represents a scientifically grounded and clinically meaningful advancement in the long-term management of RLP, particularly in aggressive and recurrent forms of the disease.